Experiences and coping behaviors of patients with psoriasis: a qualitative study - Lin-Lin Lee; An-Ping Huo; Shu-Ling Chen (Taylor & Francis Group, 2023)
Background Psoriasis is a complex, chronic, lifelong inflammatory skin disease characterized by the development of erythematous, indurated, scaly, pruritic, and often painful skin plaques, and it is currently incurable. It profoundly affects psychological wellbeing and social functioning and has significant associated co-morbidities. To improve clinical approaches, understanding of the experiences of patients with psoriasis is needed. Objective To explore the experiences and coping behaviors of patients with psoriasis. Methods A qualitative study approach was conducted. Through semi-structured interviews, 20 patients with psoriasis were recruited from general practices and specialist dermatology practices in a regional teaching hospital in Taiwan. Recorded interviews were transcribed and analyzed by content analysis. Results Three themes and nine subthemes were identified: (1) Symptoms distress: (a) trouble with scaling, (b) bothersome itching, and (c) complex pain experiences; (2) Psychological distress: (a) encountering discrimination and (b) feeling stigmatized; (3) Managing psoriasis: (a) coping with symptoms, (b) seeking alternative methods, (c) using biologic agents, and (d) changing thinking and coexisting with the disease. Conclusion The experience of patients with psoriasis has significant negative impacts on their lives. The findings of this study can provide healthcare professionals with a reference for the care of patients with psoriasis.